Le jeu entre le dit et le non-dit dans Léviathan de Julien Green - Grzybowska, Aleksandra (Romanica Silesiana)
Aleksandra Grzybowska examines the relationships between the characters of Leviathan, a novel by Julien Green, based on the manipulation, and consequently, oblique statements and mistification. Keywords: Julien Green; Léviathan; manipulation; obliqueness; mystification